Pengaruh Harga Kualitas Pelayanan Paket Data Indosat Ooredoo Terhadap Kepuasan Pelanggan Di PT. Multi Media Selular Jakarta Timur - Catharina Frisca Apriliana Aini Catharina Frisca Apriliana Aini; Abdul Gofur Abdul Gofur (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study was conducted with the aim to determine (1) the effect of price on customer satisfaction, (2) the effect of service quality on customer satisfaction, and (3) the effect of price and service quality on customer satisfaction. The study was carried out using a quantitative approach through surveys and questionnaires in accordance with statistical procedures. The data obtained were analyzed using multiple linear regression techniques with the help of the SPSS 25 program.The population in this study are customers who use the Indosat Ooredoo data plans of PT Multi Media Selular in the East Jakarta area, with a sample of 95 respondents selected through simple random sampling technique. From the results of the study it can be concluded that the price has an effect on customer satisfaction with PT Multi Media Selular products in Jakarta Timur. This means that when the price is not too high, then customer satisfaction with the products of PT Multi Media Selular in East Jakarta will increase. In addition, the service quality factor also significantly affects customer satisfaction with PT Multi Media Selular products in East Jakarta. This means that there is a unidirectional relationship between price and service quality variables and customer satisfaction variable for PT Multi Media Selular products in East Jakarta.